Effect of soluble immune complexes of Fc and C3 receptor-dependent phagocytosis by human monocytes. - Kávai, M (1981)
The capacity was studied of bovine serum albumin (BSA) rabbit anti-BSA and ovalbumin (OA) rabbit anti-OA immune complexes of different composition to inhibit the Fc receptor-dependent adherence and phagocytosis of sensitized sheep red blood cells by human monocytes. Parallel experiments were performed on the ability of the immune but complement-reacted complexes to inhibit the C3 receptor-dependent phagocytosis of C3-coated yeast particles. The extent of inhibition of both the Fc and C3 receptor-dependent phagocytosis was proportional to the antibody avidity of the complex used. Immune complexes made at equivalence and at moderate antibody excess markedly inhibited both types of phagocytosis, whereas those made at moderate antigen excess had only a weak inhibitory effect. These findings can be explained by the correlation between the Fc receptor-binding and complement-activating capacities of immune complexes of different composition. An alternative explanation, however, is also discussed.